1995
DOI: 10.1016/s1010-7940(05)80011-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous amiodarone vs propafenone for atrial fibrillation and flutter after cardiac operation

Abstract: The safety and efficacy of amiodarone and propafenone in converting atrial fibrillation or flutter after cardiac surgery were compared in a randomized double-blind trial. Eighty-four patients with sustained atrial tachyarrhythmias of more than 30 min' duration, stable hemodynamic status and neither preoperative atrial arrhythmias nor treatment with other antiarrhythmis drugs, were randomized to receive amiodarone (46 patients: 5 mg/kg over 15 min and then 15 mg/kg over the subsequent 24 h for non-converting) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 9 publications
1
30
1
Order By: Relevance
“…Amiodarone was also the preferred therapy for patients with AF who were hemodynamically stable but had low blood pressure, based on evidence showing its safety in this situation. 9,23 The IV beta-blockers or calcium-channel blockers in such patients can cause further hypotension. For patients with depressed left ventricular function and those with ejection fraction < 20%, amiodarone was recommended as first-line therapy based on its lack of negative inotropic effects and low proarrythmia potential.…”
Section: Rate Versus Rhythm Control In Light Of New Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Amiodarone was also the preferred therapy for patients with AF who were hemodynamically stable but had low blood pressure, based on evidence showing its safety in this situation. 9,23 The IV beta-blockers or calcium-channel blockers in such patients can cause further hypotension. For patients with depressed left ventricular function and those with ejection fraction < 20%, amiodarone was recommended as first-line therapy based on its lack of negative inotropic effects and low proarrythmia potential.…”
Section: Rate Versus Rhythm Control In Light Of New Evidencementioning
confidence: 99%
“…Two randomized trials assessed the efficacy of amiodarone compared with propafenone in reversing AF after cardiac surgery. 9,10 In the first study, 84 patients with sustained AF were randomized to receive IV amiodarone or IV propafenone. Within 24 h, 38 of 46 patients (82.6%) given amiodarone and 26 of 38 patients (68.4%) given propafenone converted to sinus rhythm, the difference was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…In 1 of these studies, amiodarone and flecainide had similar rates of conversion. 70 Two studies of intravenous amiodarone and propafenone in postoperative AF of 40 and 84 patients, respectively, observed little difference between drugs, although there was a small trend in each study in favor of amiodarone at 24 hours with conversion rates of 67% versus 77% (PϭNS) 75 and 68% versus 83% (PϭNS). 76 Interestingly, in both studies, early (1 hour) conversion rates were significantly better with propafenone, suggesting a more delayed onset of action with amiodarone.…”
Section: Amiodarone For Afmentioning
confidence: 99%
“…Di Biasi et al [34] compared amiodarone with propafenone in 84 patients with atrial fibrillation or flutter after cardiac surgery. They found that conversion rates at 1 h (19.5 % vs 44.7 %) were better with propafenone, but that by 24 h amiodarone was superior (82.6 % vs 68.4 %).…”
Section: Perioperativementioning
confidence: 99%